IDENTIFICATION OF INFLUENCING FACTOR ISLAMIC BASED VALUE ENTREPRENEURSHIP TOWARDS BUSINESS PERFORMANCE : A STUDY CASE IN BANDUNG - Sanjaya, M Ramadhani; Chaldun, Evy Rachmawati (Journal of Business and Management, 2018)
Â Abstract. The ratio of Indonesian entrepreneurs based on BPS data has risen to 3.1 percent. Indonesia is the largest muslim population of the world. According to BPS sensus 2010, the percentage of Muslim in Indonesia is 87,18% and from that amount some people are entrepreneur. Islam offer the concept of economic and business value that written in the Quran and what Messenger Muhammad. Therefore, is important to know how the Islamic value affect the entrepreneur spirit and mindset of muslim entrepreneur in and the impact of that Islamic value on the performance of business. This study used qualitative approach as research methodology. The method of sampling is purposive sampling. Observation and interview used to gain data from the respondent. Islamic value in business are integrity, transparency, fairness, target orientation that derived from quran and history of Muhammad SAW. The research concludes that Islamic entrepreneurship concept are align with modern theory ofentrepreneurship. The main purpose of business in Islam is to spread benefit to society as the manifestation of worship to gain blessing from god. The study find that some of muslim entrepreneur in Indonesia, know and implement that value in their business activity whereas some of them are not. The implementation of Islamic value give positive correlation on business performance, but in requirement that business strategy is designed well first. Therefore, it really recommended for all muslim entrepreneur to implement this value in their business. Â Keywords: Business Performance, Entrepreneurship, Islamic Value, Spirituality, Muslim Entrepreneur